2008
DOI: 10.1089/ten.tea.2007.0268
|View full text |Cite
|
Sign up to set email alerts
|

Cementum and Periodontal Ligament–like Tissue Formation Induced Using Bioengineered Dentin

Abstract: Stem cell-mediated root regeneration offers opportunities to regenerate a bio-root and its associated periodontal tissues to restore tooth loss. Periodontal ligament (PDL) and cementum complex and dentin pulp complex have been tissue engineered using human dental pulp stem cells and PDL stem cells, respectively. The aim of this study was to explore whether dentin formation could be induced using an inductive substrate and whether bioengineered dentin could induce cementum and PDL formation. First, dentin was b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…Despite textbook definition as separate anatomical entities, tooth root and the periodontium is functionally a single unit. [1][2][3] Approximately 64% of the U.S. population has lost at least one permanent tooth due to dental caries, periodontal disease, trauma, or genetic disorders. [4][5][6][7] The field of tooth regeneration has grown robustly.…”
Section: Introductionmentioning
confidence: 99%
“…Despite textbook definition as separate anatomical entities, tooth root and the periodontium is functionally a single unit. [1][2][3] Approximately 64% of the U.S. population has lost at least one permanent tooth due to dental caries, periodontal disease, trauma, or genetic disorders. [4][5][6][7] The field of tooth regeneration has grown robustly.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a potential tissueengineering approach to periodontal and bone regeneration involves the incorporation of progenitor cells and instructive messages in a prefabricated three-dimensional construct and subsequent implantation of the construct into the defect site [37]. Several studies have shown that autologous bone marrow mesenchymal stem cells can regenerate alveolar bone and periodontal ligament-like structures after transplantation in vivo [9,41,42]. The use of LLLI on these biomaterials before transplantation could lead to a faster and greater regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Bioengineering strategies have targeted tooth regeneration using various combinations of scaffolds, growth factors and cells [81][82][83][84]. Approaches using tissue recombinations, and pelleting cells in a scaffold-free environment, are also popular strategies for whole-tooth engineering [85,86].…”
Section: Whole-tooth Engineeringmentioning
confidence: 99%
“…In order for these approaches to achieve clinical status, what remains to be understood and perfected is how best to maintain the spatial organization of the dental epithelial and dental mesenchymal tissues, to guide not only the shape and size of a tooth and surrounding alveolar bone, but also to achieve proper compartmentalization of individual tissue types [92]. For instance, studies have observed ectopic alveolar bone growth within dental tissues [81,96]. Likewise, the ECM components associated with functional tooth-root formation and for functional tooth eruption are critical to our understanding.…”
Section: Whole-tooth Engineeringmentioning
confidence: 99%